Forgiveness in seconds Analytical Grammar Study (Journal of the College of Basic Education, 2023)
The rule of forgiveness in grammar is one of the rules that were commonly used by grammarians and commentators who used to resort to it in directing a verse, verse, or prose speech that contradicted the well-known rules they set, so they used to apologize for that by saying that what is unforgivable in the follower is forgiven, for example.We can point out that the forgiveness mentioned by the scholars falls within the rule of broadening or expanding the meaning or wording mentioned by Al-Suyuti and other grammarians.Expansion may include many grammatical provisions such as introduction and delay, or such as their saying that it expands in an adverb that does not expand in others, and so on.However, this research will deal with the study and analysis of their saying (forgivable in the seconds what is unforgivable in the first) and so on, and it is one of the sub-grammar referred to by some jurists and fundamentalists. Primarily, the opinions of grammarians and rhetoricians.Referring to the naming of the base and the multiple names it was called, as well as addressing the dispute between grammarians in accepting or rejecting it, or standing in a middle place between those and those.